Short communication: Virulence of barley leaf rust in the South of Russia in 2017-2019 - Danilova, Anastasiya V.; Volkova , Galina V. (Spanish Journal of Agricultural Research, 2022)
Aim of study: To analyze the structure of Puccinia hordei populations by virulence in southern Russia during 2017-2019.Area of study: South of Russia, the leading Russian region for barley production where barley leaf rust is an important foliar disease.Material and methods: Uredinial samples of P. hordei were collected at the production sites of winter barley in the south of Russia. Single uredinial isolates (total 95) were tested for virulence with 17 differentials with Rph resistance genes.Main results: No isolates were found virulent to the host line with the Rph13 gene. There was a decrease in the number of fungal isolates virulent to the host lines with Rph5 and Rph7 genes. In 2017 and 2019, isolates containing a large number of virulence alleles (from 11 to 15) prevailed. In 2018, isolates with low (1-5) and medium (6-10) frequency of virulent alleles prevailed, as well as avirulent isolates. The values of the Nei index via diversity showed high similarity of the pathogen populations in 2017-2018 (N = 0.05) and minor differences in 2017-2019 and 2018-2019 (N = 0.13 and 0.16, respectively). The greatest frequency of virulence alleles in accordance with the Nei (Hs) index was noted for the 2018 population (Hs = 0.36). For the 2017 and 2019 populations, this indicator was on average Hs = 0.29 and 0.20, respectively.Research highlights: Analysis of genetics of the P. hordei population is important for the strategy of varietal distribution in the region and development of rust-resistant cultivars.